Holistic modeling of composites manufacturing using poromechanics. (2nd January 2016) - Rouhi, Mohammad S.; Wysocki, Maciej; Larsson, Ragnar
Abstract: In the present paper, we present a novel finite-element method capable of handling most of the physics arising in the resin wet-out step for any composite system and processing case. The method is based on a compressible two-phase continuum formulation where a key feature is to model the involved physics via innovative use of the compressibility of the phases. On the one hand, the fluid-phase compressibility is used to capture the physics of the advancing resin front as well as the physics behind the flow front. On the other hand, solid-phase compressibility is used to model micro-infiltration of the resin and the corresponding preform compaction, essentially considered as a fluid sink problem. Finally, the generic porous media model is formulated in the finite strain regime. The model is implemented and demonstrated for different manufacturing methods and the results with respect to each example are presented. The degree of saturation, pressure distribution, preform deformation, and reaction forces are some of the post-processed results for different manufacturing methods. The ultimate goal of this contribution is to establish a unified generic and general simulation tool for structural (long fiber) composite processing where, to this date, there is no single FE-based tool available commercially for this purpose. Abstract :